Peran Pemerintah Daerah dalam Pemenuhan Hak Atas Keadilan - Donny Michael (Jurnal HAM, 2014)
Someone who is "capable" and has a legal problem, he may appoint a person or advocate to defend its interests. Similarly, someone who is classified as "not capable" of defense can also request a public defender or as a worker in legal aid to defend its interests in a lawsuit. This study uses a descriptive-analytical study with a qualitative approach, in which the primary data came from informants. While secondary data in the form of literature from books, scientific manuscripts, research reports, and documents related to the research topic. The results of this study illustrate that the presence of the three patterns is a model implementation is the provision of legal aid legal aid non-litigation, litigation and non-litigation and litigation combined. Local government agencies, law enforcement, advocates agencies, and universities are different attempts to realize the implementation of the legal aid "probono". These efforts can be made in institutional policies and individual officials concerned. The people generally are not aware of any right to legal aid. Instead, the agency that provides legal assistance funds such as local government and the courts are not transparently deliver legal aid funding is available to the public.